Border proximity, ports, and railways: Analyzing their impact on county-level economic dynamics in Hungary, 2001-2020 - Roman Fedorenko; Galina Khmeleva; Marina Kurnikova (Economies, 2023)
In this research, our primary objective is to dissect the influence of specific locational elements-proximity to international borders, substantial ports, and significant railway junctions- on the economic vitality of Hungary's counties from 2001 to 2020. The aim is to reveal how these factors individually contribute to economic disparities and to demonstrate their compounded effect on regional prosperity. This analysis is particularly timely and pertinent as regional inequalities are becoming more pronounced globally, making understanding such disparities crucial for effective policy formulation and regional planning. Utilizing GDP per capita as a fundamental indicator of economic health, we meticulously categorized counties, revealing a clear correlation between these locational advantages and economic performance. We innovatively employed Python to script a unique code, creating a matrix that enriches the presentation of our results, thereby facilitating a more nuanced understanding of these correlations. Our findings are significant in the current socio-economic climate, highlighting the need for tailored strategies considering unique regional attributes. This study is instrumental for policymakers and stakeholders in formulating informed, targeted strategies to harness these locational advantages, fostering balanced development, and narrowing the economic divide within the nation. The actuality of our research lies in its immediate relevance, offering insights critical to current discussions and decisions in regional development planning.
Keywords: 330; gross domestic product per capita; growth rate; border regions; ports; railroads